AKUNTANSI LINGKUNGAN KAJIAN PENERAPAN PADA PERUSAHAAN YANG TERDAFTAR DI BEI - Qodriana, Ersa Lailatul; Nurdiwaty, Diah (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2017)
This research is based on the observation of researchers that there are still many companies that ignore the interests of the environment. Day by day the problems of the environment are getting out of hand, and this makes a serious problem among thinkers. The cause of environmental problems is caused by the activities of companies in Indonesia. Now there is a rule in accounting for the impact caused to the environment. Environmental accounting is one of the rules that aims to provide information to stakeholders. The problems of this research are (1) The Influence of Environmental Cost on Application of Environmental Accounting (2) The Influence of Return On Asset To The Application Of Environmental Accounting (3) The Influence Of The Type Of Company To The Application Of Environmental Accounting. In this study, using descriptive quantitative approach. Sampling using purposive sampling technique. The total sample used in the study were 16 companies. While the data analyst using logistic regression, the independent variable is environmental cost (X1), ROA (X2) and company type (X3), while for the dependent variable is the application of environmental accounting. The conclusion of this study is that environmental costs are the main consideration in the application of environmental accounting, environmental costs and accounting are interrelated. Companies that have a high ROA many do not apply environmental accounting. The types of companies that apply the most environmental accounting are manufacturing and service companies.